Clinical pharmacokinetic study of tacrolimus in continuous intravenous administration for lung transplantation - Sohn, You Min; Ko, Ryoung Eun; Park, Hyo Jung; Choo, Eunjung; Jung, Minji; Lee, Sukhyang; Jeon, Kyeongman (Journal of Thoracic Disease, 2023)
Tacrolimus is a cornerstone of immunosuppression after lung transplantation. However, there are no clear guidelines on how to administer the drug and the duration to achieve the required therapeutic range in the early phase of lung transplantation. This is a single-center cohort study of adult patients who had lung transplantation. Tacrolimus was administered beginning with a low dose of 0.01 mg/kg/day immediately after transplantation. In addition, the designated clinical pharmacist conducted a daily intervention with trough concentrations to achieve the target of 10–15 ng/mL. Time in the therapeutic range (TTRin, %), time to the therapeutic range (TTRto, days), and coefficient of variation (CoV) of tacrolimus were evaluated for the 2-week post-transplant period. A total of 67 adult patients who had received first-time lung transplantation were included in the analysis. The median percentage of tacrolimus TTRin was 35.7% (21.4–42.9%) for the 2-week postoperative period. The median day of TTRto was 7 days (5–9 days), and the median tacrolimus trough concentration was 10.02 ng/mL (7.87–12.26 ng/mL) for the 2-week postoperative period. The median CoV of tacrolimus was 49.7% (40.8–61.6%). Acute kidney injury following tacrolimus infusion occurred in 23 (34.3%) patients, but there was no neurotoxicity or acute cellular rejection within 1 month of the postoperative period. In conclusion, continuous intravenous administration with the daily measure and dose titration of tacrolimus trough concentrations allowed the therapeutic range of tacrolimus to be reached within 1 week without significant adverse events, although the pharmacokinetic parameters were highly variable over time.
Keywords: intravenous infusion; lung transplantation; Tacrolimus; therapeutic drug monitoring